2012
DOI: 10.1590/s0004-27492012000100002
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness comparison between non-penetrating deep sclerectomy and maximum-tolerated medical therapy for glaucoma within the Brazilian National Health System (SUS)

Abstract: RESUMO Objetivo: A esclerectomia profunda não penetrante (EPNP) é uma opção viável para o tratamento cirúrgico do glaucoma de ângulo aberto. O objetivo deste estudo é avaliar a relação custo-efetividade da EPNP e compará-la com terapia clínica máxima (TCM) em ABSTRACTPurpose: Nonpenetrating deep sclerectomy (NPDS) has emerged as a viable option in the surgical management of openangle glaucoma. Our aim is to assess the cost eff ectiveness of NPDS and to compare it to maximum medical treatment in a 5year followu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
(15 reference statements)
1
6
0
Order By: Relevance
“…Similar to our study is that of Guedes et al, which used a decision analysis model for a 5-year time horizon from the point of view of the Brazilian Public National Health System (49). The study evaluated treatments post application of topical medication and found that non-penetrating deep sclerectomy (NPDS) is less costly and more effective than medical therapy when three topical medications are required (50). The fact that the cost increases with advanced glaucoma, this suggests that therapy is necessary in the earlier stage of glaucoma (47).…”
Section: Discussionsupporting
confidence: 56%
“…Similar to our study is that of Guedes et al, which used a decision analysis model for a 5-year time horizon from the point of view of the Brazilian Public National Health System (49). The study evaluated treatments post application of topical medication and found that non-penetrating deep sclerectomy (NPDS) is less costly and more effective than medical therapy when three topical medications are required (50). The fact that the cost increases with advanced glaucoma, this suggests that therapy is necessary in the earlier stage of glaucoma (47).…”
Section: Discussionsupporting
confidence: 56%
“…96 Using a decision analysis model, Guedes et al suggested that, for a 5-year period in the Brazilian Public National Health System, NPDS is less costly and more effective than medical therapy when three topical medications are required. 97 However, they have excluded the cost of transportation, medical visits, examinations, and indirect costs. They also showed that the cost increases with advanced glaucoma, thus advocated to perform NPDS in the earlier stage of glaucoma.…”
Section: Treatment Of Glaucoma Primary Open Angle Glaucomamentioning
confidence: 99%
“…Three CUAs compared surgery and topical medications. In a 2012 study adopting a Brazilian healthcare perspective, Paletta Guedes et al [18] estimated that surgery (nonpenetrating deep sclerectomy) was a dominant option versus three adjunct therapies of prostaglandin analogues with timolol and dorzolamide in patients reaching the maximum medication dose. In 2015, Kaplan et al [19] explored the cost effectiveness of the Baerveldt implant versus trabeculectomy with mitomycin from a USA societal perspective and presented a positive ICER of $US29,055 per QALY for the Baerveldt implant.…”
Section: Surgical Treatmentsmentioning
confidence: 99%